2010
DOI: 10.1186/1471-2350-11-104
|View full text |Cite
|
Sign up to set email alerts
|

Novel deletion alleles carrying CYP21A1P/A2chimeric genes in Brazilian patients with 21-hydroxylase deficiency

Abstract: BackgroundCongenital adrenal hyperplasia due to 21-hydroxylase deficiency is caused by deletions, large gene conversions or mutations in CYP21A2 gene. The human gene is located at 6p21.3 within a locus containing the genes for putative serine/threonine Kinase RP, complement C4, steroid 21-hydroxylase CYP21 tenascin TNX, normally, in a duplicated cluster known as RCCX module. The CYP21 extra copy is a pseudogene (CYP21A1P). In Brazil, 30-kb deletion forming monomodular alleles that carry chimeric CYP21A1P/A2 ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 49 publications
0
18
0
1
Order By: Relevance
“…No sequencing analysis was presented to narrow down the precise junction sites, however. In addition, haplotype IV in the Brazilian study might represent the same kind of chimera as the CH-8 chimera identified and so designated in our study (31). …”
Section: Discussionmentioning
confidence: 62%
See 3 more Smart Citations
“…No sequencing analysis was presented to narrow down the precise junction sites, however. In addition, haplotype IV in the Brazilian study might represent the same kind of chimera as the CH-8 chimera identified and so designated in our study (31). …”
Section: Discussionmentioning
confidence: 62%
“…Proband 7 and sibling patient 7S have NC CAH, findings that are in accord with their carrying CH-9 on one allele and V281L, a common NC mutation, on the other. Interestingly, 2 patients with moderate SV phenotypes in the Brazilian study carried a second chimera allele (haplotype VIII) that seems to have a junction site similar to CH-9 (31). No sequencing analysis was presented to narrow down the precise junction sites, however.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Normalized relative values ranging from 0·7 to 1·3 corresponded to two gene copies in the genotype (normal). This confidence interval was established by data obtained with five controls in each MLPA assay (Supporting information).…”
Section: Methodsmentioning
confidence: 99%